A Review Paper on Data Mining Concepts and Its Techniques: Exploring the Concept and Techniques of Data Mining (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper offers an overview to the basic concept of data mining. That provides an explanation how data mining is used to collect meaningful information and to establish significant relationships between variables contained in a large data set data warehouse. In the case study reported in this paper, a data mining approach is used to extract knowledge from a data set. Data mining is one of the most critical information exploration phases in the database cycle and is known to be a major sub-field of knowledge management. Data mining activity continues to grow in market and learning organizations over the coming decades. A review paper discusses the uses of data mining technologies that have been developed to help the information management method.